2013
DOI: 10.1186/1749-8090-8-192
|View full text |Cite
|
Sign up to set email alerts
|

A flow visualization model of duodenogastric reflux after esophagectomy with gastric interposition

Abstract: BackgroundOur goal was to verify surgical factors that affect duodenogastric reflux (DGR) after esophagectomy through the use of a flow visualization model that would mimic an intrathoracic gastric tube.MethodsTransparent gastric tube models for different routes (retrosternal space [RS] and posterior mediastinum [PM]) were fabricated. Various distal pressures were applied to the experimental model filled with water, and the flow was recorded with a high-speed camera. The volume and maximum height of the reflux… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…8 In addition, gastric content may readily flow backward into the esophagus in the thoracic cavity due to negative pressure. 9 Mohiuddin and Low described a higher rate of gastric conduit redundancy in the right hemithorax among patients who underwent Ivor-Lewis esophagectomy manifesting as delayed gastric emptying. 10 In our study, we found that intrathoracic location of the conduit plays a role in the development of these inflammatory changes.…”
Section: Discussionmentioning
confidence: 99%
“…8 In addition, gastric content may readily flow backward into the esophagus in the thoracic cavity due to negative pressure. 9 Mohiuddin and Low described a higher rate of gastric conduit redundancy in the right hemithorax among patients who underwent Ivor-Lewis esophagectomy manifesting as delayed gastric emptying. 10 In our study, we found that intrathoracic location of the conduit plays a role in the development of these inflammatory changes.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, DGR can be caused by any factor that leads to gastrointestinal motility disorders and anatomical abnormalities, such as major gastrectomy ( 31 ), disruption of gastrointestinal hormone secretion ( 32 ) and autonomic dysfunction ( 33 ). Among them, disorders of gastrointestinal hormone secretion have a greater impact on primary DGR.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, there has been found up to 20% esophagitis in the cervical esophageal stump during the first year after surgery, and approximately 70% in the seventh year, and the presence of Barrett's esophagus in the cervical stump in up to 27.7% of cases, which is more serious 26,34 . Of course, the destruction of reflux containment mechanisms (loss of inferior esophageal sphincter mechanism, cardia and pylorus), promote mixed reflux (acid and bile), extremely harmful to the esophageal mucosa 36,37 .…”
Section: Discussion Discussion Discussion Discussionmentioning
confidence: 99%